Pemberdayaan UMKM Desa Bontomarannu melalui Pelatihan Produk Hasil Pertanian oleh Mahasiswa KKN STIM Lasharan Jaya untuk Mengatasi Masalah Surplus Panen - Galib, Mukhtar; Fadjriyah, Sitti; Nurhasaroh, Siti; Syalsabillah, Nur Fadillah; Adhitia, Fitrah; Langi, Irensi Laen; Tio, Septianis Adis; Armita, Armita (ABDI DAYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Bontomarannu Village, one of the main vegetable producers in Bantaeng Regency, faces a recurring issue of surplus harvests that are often poorly distributed, resulting in agricultural products piling up and spoiling. To address this problem, students from STIM Lasharan Jaya initiated a training program on agricultural product processing for the community, particularly targeting the women of the PKK group. The training aimed to enhance the capacity of local SMEs in transforming surplus harvests into value-added products, such as spinach chips and tomato juice. The method involved theoretical sessions, hands-on practice, and interactive discussions to address challenges and explore product development opportunities. The results showed significant improvements in participants' skills in processing agricultural products, including hygienic and appealing packaging techniques. Additionally, support from the village head and sub-district leader provided motivation and additional facilities to ensure the program's sustainability. This initiative serves not only as a short-term solution to the surplus harvest issue but also opens new opportunities to improve the economic conditions of Bontomarannu Village sustainably